2023
DOI: 10.1039/d2fo03912e
|View full text |Cite
|
Sign up to set email alerts
|

Protein blends and extrusion processing to improve the nutritional quality of plant proteins

Abstract: Utilizing protein blends improved the amino acid profile of the ingredients, and extrusion processing effectively reduced trypsin inhibitors in all extrudates but only enhanced the in vitro protein digestibility of the pulse-rich extrudates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
(76 reference statements)
1
2
0
Order By: Relevance
“…Extrusion significantly increased the IVPD of DDGS (P < 0.05) (Fig. 6(A)), which was confirmed by a previous study by Duque-Estrada et al 7 According to existing studies, the shift in protein secondary structure from ⊎-sheet to ⊎-turn usually leads to an increase in IVPD. 41 In the present study, however, the opposite shift was observed, but there was still an increase in IVPD.…”
Section: In Vitro Protein Digestibilitysupporting
confidence: 87%
See 1 more Smart Citation
“…Extrusion significantly increased the IVPD of DDGS (P < 0.05) (Fig. 6(A)), which was confirmed by a previous study by Duque-Estrada et al 7 According to existing studies, the shift in protein secondary structure from ⊎-sheet to ⊎-turn usually leads to an increase in IVPD. 41 In the present study, however, the opposite shift was observed, but there was still an increase in IVPD.…”
Section: In Vitro Protein Digestibilitysupporting
confidence: 87%
“…Extrusion puffing treatment increases in vitro protein digestibility (IVPD) of texturized vegetable proteins and improves its quality. 7 A study published by Wang et al, 8 showed that after extrusion treatment, the surface structure, amino acid composition and protein structure of extruded distillers grains changed, the content of soluble dietary fiber increased, and the nutritional value improved. However, there is little research on extrusion puffing modification of DDGS.…”
Section: Introductionmentioning
confidence: 99%
“…Different foods vary in composition of amino acids and digestibility between the dietary proteins. All amino acids are important for normal functioning and synthesis of muscles and organs, enzymes, hormones and immune system (Duque‐Estrada et al., 2023).…”
Section: Challengesmentioning
confidence: 99%